1993
DOI: 10.1002/eji.1830230816
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial expression of a single‐chain Fv fragment which efficiently protects the acetylcholine receptor against antigenic modulation caused by myasthenic antibodies

Abstract: Monoclonal antibodies (mAb) against the main immunogenic region (MIR) of the acetylcholine receptor (AChR) are very potent in inducing antigenic modulation of the AChR in animals and in muscle cell cultures. A recombinant antibody fragment of the rat anti-MIR mAb198 was cloned by polymerase chain reaction and expressed as soluble single-chain Fv fragment (scFv198) in E. coli and affinity purified. DNA sequencing was used to define the VH (IB) and VL (K2) chain gene usage. scFv198 was found immunologically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
4

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 44 publications
1
25
0
4
Order By: Relevance
“…functional single chain Fv fragment has been constructed and expressed in Escherichia coli (Mamalaki et al, 1993).…”
Section: Crystallization Of Fab Fragment Of Pathogenic Rat Mab Againsmentioning
confidence: 99%
“…functional single chain Fv fragment has been constructed and expressed in Escherichia coli (Mamalaki et al, 1993).…”
Section: Crystallization Of Fab Fragment Of Pathogenic Rat Mab Againsmentioning
confidence: 99%
“…The prominent pathogenicity of anti-MIR mAb has been extensively documented by in vitro and in vivo studies (reviewed in [6]). It has been shown that univalent anti-MIR antigenbinding fragments (Fab) or scFv antibody fragments can efficiently inhibit a large portion of autoantibodies from binding to the AChR [7,8]. Furthermore, Fab and scFv fragments can efficiently protect the receptor against antigenic modulation induced by anti-MIR mAb or MG sera [7,8] and thus are good candidates for a therapeutic approach.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that univalent anti-MIR antigenbinding fragments (Fab) or scFv antibody fragments can efficiently inhibit a large portion of autoantibodies from binding to the AChR [7,8]. Furthermore, Fab and scFv fragments can efficiently protect the receptor against antigenic modulation induced by anti-MIR mAb or MG sera [7,8] and thus are good candidates for a therapeutic approach. However, the immunogenicity of rodent antibodies in humans prevents their application in clinical procedures.…”
Section: Introductionmentioning
confidence: 99%
“…hAChR antigenic modulation and protection on CN21 cells hAChR antigenic modulation and protection were performed as described [8]. CN21 cells grown to confluency in 48-well tissue culture plates were incubated, in the presence of 40 lg/ ml cycloheximide, first with 10 lg/ml of anti-hAChR Fab, or the negative control Fab TT [26], or culture medium, and then with either 10 lg/ml of goat anti-human F(ab') 2 antibody or an MG serum dilution resulting in 90% of maximal antigenic modulation in the absence of competitor.…”
Section: Riamentioning
confidence: 99%
“…Analysis of the isolated antibody clones would also extend existing information on the human anti-AChR autoreactive repertoire. Anti-MIR antibody fragments have been previously used to protect AChR from pathogenic autoantibody action [7][8][9]. However, the isolation of a panel of AChR "protectors" directed against the most dominant immunogenic AChR epitopes is probably required for the development of an efficient therapeutic pool.…”
Section: Introductionmentioning
confidence: 99%